Changing discourses of Chinese language maintenance in Australia: unpacking language ideologies of first-generation Chinese immigrant parents from People’s Republic of China - Wang, Yining; Li, Jia (Frontiers in Psychology, 2024)
Parental agency of their children’s language learning is often determined by their perceptions of the significance of the language in both family and society levels. Based on a larger ethnography conducted in Sydney from 2017 to 2020, this study investigates the language ideologies of Chinese immigrant parents from the People’s Republic of China in the recent decades, regarding the maintenance of their children’s Chinese heritage language(s). Drawing on the concept of language as pride and profit shifting between communities across time and space, this study reveals that Chinese parents primarily emphasize the economic benefits associated with Chinese languages when it comes to preserving their heritage language(s). While the significance of cultural pride and identity remains evident, there is a notable shift where the concept of pride is merging with that of profit concerning the importance of Chinese heritage language. However, the commodification of Chinese and identity, privileging “national” mandarin while marginalizing “regional” others, impedes the transmission of diverse Chinese heritage languages other than Mandarin. Simultaneously, the value-laden calculation of language prioritizes the “most” prestigious English, often at the expense of “heritage” Mandarin, regardless of its acknowledged economic potential. The findings illustrate how language ideologies and practices within the Chinese diaspora are shaped by power conflicts between English and Mandarin Chinese, hierarchical distinctions between Mandarin and non-Mandarin Chinese, and subtle stratification within regional Chinese languages. The research underscores the challenges faced by minority communities in preserving their heritage languages, particularly those with limited economic capital or political influence.